High serum free IL-18 is associated with decreased omalizumab efficacy: findings from a 2-year omalizumab treatment study. (2nd September 2021) - Morimoto, Chie; Matsumoto, Hisako; Tajiri, Tomoko; Gon, Yasuhiro; Ito, Reiko; Hashimoto, Shu; Suzukawa, Maho; Ohta, Ken; Izuhara, Kenji; Ono, Junya; Ohta, Shoichiro; Ito, Isao; et al.
Abstract: Objective: Omalizumab is more effective in severe allergic patients with eosinophilic asthma than those with non-eosinophilic asthma. IL-18, a unique cytokine involved in allergic but non-eosinophilic inflammation, might be associated with the latter condition. We aimed to clarify the roles of IL-18 related pathways in insufficient response to omalizumab treatment. Methods: Patients with severe allergic asthma who completed 2-year omalizumab treatments at Kyoto University Hospital were included in this study (UMIN000002389). Associations between pretreatment levels of serum free IL-18 in addition to other mediators and asthma phenotypes including responses to omalizumab treatment were analyzed. Changes in serum free IL-18, periostin and total IgE levels during the treatment were also examined. Results: Twenty-seven patients (19 females, average age of 55.7 years) were examined. Fifteen incomplete responders who experienced exacerbations in the second year, were significantly and more frequently obese and showed significantly earlier asthma onset, lower blood eosinophils and more exacerbations before omalizumab treatment than complete responders. Significantly more patients showed high baseline serum free IL-18 levels (≥141 pg/mL, a threshold for the highest tertile) among the incomplete responders than complete responders. Patients with high serum free IL-18 levels shared similar characteristics with incomplete responders, showing significant reductions in serum total IgE levels during omalizumab treatment. Finally, serum free IL-18 levels negatively correlated with serum periostin levels at baseline and in change ratios. Conclusions: High baseline serum free IL-18 levels may predict reduced omalizumab efficacy in severe allergic patients with type-2 low asthma, regarding reduction of exacerbations.